‘Culture’, criminality and collective mindset: political financing in Brazil - Valarini, Elizângela (Political corruption and organizational crime, 2021)
The issue of corruption has occupied a central place in Brazilian public life in recent decades. In 2016, yet another president of the republic was impeached on suspicions and charges of corruption. The problem of corruption seems to have become part of Brazilians’ daily lives, causing a feeling of revolt in the society, strengthening anti-corruption policies and modifying the political landscape, in particular by the last presidential elections, with the victory of Jair Bolsonaro. How politics and business are linked in Brazil was exposed in recent scandals, especially by Mensalão and Operação Lava Jato (Operation Car Wash), which was its modus operandi. Through informal relationship between politicians and businessmen, which in parts served to finance political parties and electoral campaigns, private enterprises gain a privileged position to have influence in the political sphere.
Gesehen am 17.12.2021